The Administration of Lemon and Paper Mint Aromatherapy towards Reduction of Emesis Gravidarum in Pregnant Women in Trimester I at Health Center Malangbong, Garut Regency in 2022 - Hamidah; Bunga Tiara Carolin; Nurul Husnul Lail (Nursing and Health Sciences Journal (NHSJ), 2022)
Nausea and vomiting occur in the first trimester of pregnancy. Nausea in early pregnancy can be overcome by using lemon and peppermint aromatherapy. This study aimed to find out the comparison between giving lemon and peppermint aromatherapy to reducing emesis gravidarum in first trimester pregnant women. The design used in this study was a quasi-experimental design with a two-group pretest-posttest design. The sample in this study amounted to 60 respondents consisting of 30 respondents with lemon aromatherapy and 30 respondents with peppermint aromatherapy with purposive sampling technique. Data were analyzed using paired T-Test and Independent T-Test. The results of the univariate analysis of the average difference of emesis gravidarum on the administration of lemon aromatherapy was 6.33 and on the administration of peppermintaromatherapy 3.18. The results of the bivariate analysis of the difference in emesis gravidarum of pregnant women in the first trimester between the administration of lemon aromatherapy and peppermint aromatherapy had a significance value of 0.000. Giving lemon aromatherapy to reduce emesis of gravidarum in pregnant women is more effective than giving peppermint aromatherapy. Health workers are expected in addition to providing counseling, giving lemon and peppermint aromatherapy can be applied to therapy for those who experience nausea and vomiting, especially for pregnant women so that mothers feel comfortable without experiencing side effects.